2009
DOI: 10.1111/j.1755-6724.2009.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Guandishan Granitoids of the Paleoproterozoic Lüliang Metamorphic Complex in the Trans‐North China Orogen: SHRIMP Zircon Ages, Petrogenesis and Tectonic Implications

Abstract: The Paleoproterozoic Lüliang Metamorphic Complex (PLMC) is situated in the middle segment of the western margin of the Trans‐North China Orogen (TNCO), North China Craton (NCC). As the most important lithological assemblages in the southern part of the PLMC, Guandishan granitoids consist of early gneissic tonalities, granodiorites and gneissic monzogranites, and younger gneissic to massive monzogranites. Petrochemical features reveal that the early gneissic tonalities and granodiorites belong to the medium‐K c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Dongling gneiss: Xing et al 1993; Kongling high-grade terrane: Zheng et al 2006;references therein), much similar to the metamorphism in Trans-North China orogen (1887-1785 Ma), as revealed by broad isotopic studies (e.g. Trap et al 2007;Liu et al 2009b;Zhao and Zhai 2013;references therein). Therefore, the upper Permian sandstones yield age probability density functions consistent with the Qinling, Qilian, and Kunlun orogens along the southern margin of the North China Craton (Figure 12a).…”
Section: Upper Permianmentioning
confidence: 94%
“…Dongling gneiss: Xing et al 1993; Kongling high-grade terrane: Zheng et al 2006;references therein), much similar to the metamorphism in Trans-North China orogen (1887-1785 Ma), as revealed by broad isotopic studies (e.g. Trap et al 2007;Liu et al 2009b;Zhao and Zhai 2013;references therein). Therefore, the upper Permian sandstones yield age probability density functions consistent with the Qinling, Qilian, and Kunlun orogens along the southern margin of the North China Craton (Figure 12a).…”
Section: Upper Permianmentioning
confidence: 94%
“…Lithological studies display that most 2.2-2.0 Ga granitiods have medium-to coarse-grained textures and were more or less deformed. Such as granitoids are also widely recognized in the Wutai-Lüliang areas of the middle TNCO (Zhao et al, 2002(Zhao et al, , 2007(Zhao et al, , 2008bWilde et al, 2005;Trap et al, 2008;Liu et al, 2009cGeng et al, 2006b). Their geochemical studies revealed that these granitoids formed in a tectonic setting related to a continental margin/island arc (Liu et al, 2002Zhao and Zhai, 2013 and references cited therein) or in an extensional setting related to back-arc basin rifting (Du et al, , 2013, and then subjected two metamorphic events at ∼1.95 Ga and ∼1.85 Ga, respectively (Zhao and Zhai, 2013;Wei et al, 2014 and references cited therein).…”
Section: 2-20 Ga Magmatism In the Ob Basementmentioning
confidence: 95%
“…Some of these granitic rocks are deformed with gneissic schistosity conformable with that of their host rocks (e.g., Mafeng monzogranites, Li and Zhao, 2007; tonalites in the Jiehekou Group/Complex, Zhao et al, 2008b); whereas others are largely undeformed (e.g., Tonghua A-type granites, Lu et al, 2004b; and Lingyunkou A-type granites, Zhao et al, 2011). Granodiorites and tonalites are mostly in the center of the NCC (Geng et al, 2000;Kröner et al, 2005;Liu et al, 2009b;Wang et al, 2010c;Wilde, 1998;Wilde et al, 2005;Zhao et al, 2008aZhao et al, ,b, 2011, charnockites are in the west (Peng et al, 2012a), monzogranites and biotite granites are mostly in the east (Guo and Li, 2009;Lu et al, 2004a,b;Wu et al, 2007;Zhao et al, 2006), with some in the center (Geng et al, 2000;Zhao et al, 2002a), and S-type granites are mainly in the west (Peng et al, 2012a). Some 1930-1880 Ma aluminum-rich (S-type?)…”
Section: -1880 Ma Igneous Rocks In the North China Cratonmentioning
confidence: 96%
“…The 2200-1880 Ma granitic rocks include a variety of granodiorites, charnockites, tonalites, monzogranites, biotite granites and garnet/ sillimanite-bearing granites (Geng et al, 2000;Guo and Li, 2009;Kröner et al, 2005;Li and Zhao, 2007;Liu et al, 2009b;Lu et al, 2004a,b;Peng et al, 2012a;Wan et al, 2006;Wang and Wilde, 2002;Wang et al, 2010c;Wilde, 1998;Wu et al, 2007;Yang et al, 2009Yang et al, , 2011Zhao et al, 2002aZhao et al, , 2006Zhao et al, , 2008aZhao et al, ,b, 2011. Some of these granitic rocks are deformed with gneissic schistosity conformable with that of their host rocks (e.g., Mafeng monzogranites, Li and Zhao, 2007; tonalites in the Jiehekou Group/Complex, Zhao et al, 2008b); whereas others are largely undeformed (e.g., Tonghua A-type granites, Lu et al, 2004b; and Lingyunkou A-type granites, Zhao et al, 2011).…”
Section: -1880 Ma Igneous Rocks In the North China Cratonmentioning
confidence: 96%